1064 Assessment of human exposure to 1-nitropyrene by means of the determination of hydroxynitropyrenes in 896 urine samples. (24th April 2018) - Tranfo, G; Pigini, D; Paci, E; Bauleo, L; Ancona, C; Forastiere, F
Abstract : Introduction: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous organic pollutants, whose sources include traffic emissions derived from diesel/gasoline vehicles. Monohydroxylated PAHs (OH-PAHs), urinary metabolites of PAHs, were used as biomarkers of PAHs exposure. 1-Nitropyrene is a molecular marker for diesel exhaust, a significant contributor to the toxicity associated with particulate matter. Urinary metabolites of 1-Nitropyrene were recently evaluated for their utility as markers of exposure to diesel exhaust. Methods: Among the three isomers 3-, 6-, and 8-hydroxy-nitropyrene (3-, 6-, 8-OHNPy), 6-OHNPy was selected for this study as it is the most abundant found in human urine. 896 urine samples were collected from subjects randomly selected from municipality registers of Civitavecchia (Central Italy) as a part of the 'ABC Human Biomonitoring study' and tested after enzymatic hydrolysis of the glucuronic acid conjugates using HPLC-MS/MS. Pure standard of 6-OHNPy was purchased following custom synthesis and deuterium labelled 1-hydroxypyrene was used as internal standard for quantitative determination. Result: Results show that more than 50% of the 896 samples did not contained detectable concentrations of total hydroxy-nitropyrenes measured as 6-OHNPy (<0.0005 µg/g of creatinine), while 383 samples showed measurable levels, in the range 3.81–0.0005 µg/g of creatinine. Mean value is 0.091 µg/g of creatinine. Discussion: This is the first large study reporting urinary levels of 6-hydroxynitropyrene in subjects non-occupationally exposed to 1-nitro-pyrene. Previous studies showed that this biomarker is scarcely influenced by smoking. As the performances of the method allow environmental exposure assessment, where high sensitivity is needed, it can be used with even greater confidence for studies of occupational exposure assessment to diesel exhaust, where higher exposure levels are expected: the urinary levels here reported can be considered as reference values to be compared to the levels produced by occupational exposures.